2022
DOI: 10.3390/molecules27072343
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Nanoparticles Obtained by Green Synthesis as an Alternative to Improve the Germination Characteristics of L. esculentum

Abstract: Tomato is an important crop due to its nutritional contributions and organoleptic properties, which make it an appetizing vegetable around the world. In its sowing, the use of seed is the most accessible propagation mechanism for farmers. However, the induction to germination and emergence is often limited in the absence of stimulants that promote the development and growth of the seedling, added to the interference of infectious agents that notoriously reduce the vitality and viability of the seed. Given this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 53 publications
0
5
0
6
Order By: Relevance
“…Singh et al [32] indicated that green ZnO-NPs (35 nm) applied at 62 ppm showed the most significant improvement in wheat seed germination and seedling growth relative to other concentration levels. Asmat-Campos et al [33] also revealed that concentrations of ZnO-NPs (30 nm) close to 100 ppm (63.59 and 99.076 ppm) are the best to enhance tomato seeds germination since they promote metabolic activity to induce cell elongation, no phytotoxicity was observed. Itrouthwar et al [34] also evaluated ZnO-NPs (37 nm) in maize; they found that the concentration of 100 ppm exhibited the highest seed germination rate and seedling growth parameters as compared with zinc acetate (ionic control) and water (normal control).…”
Section: Discussionmentioning
confidence: 97%
“…Singh et al [32] indicated that green ZnO-NPs (35 nm) applied at 62 ppm showed the most significant improvement in wheat seed germination and seedling growth relative to other concentration levels. Asmat-Campos et al [33] also revealed that concentrations of ZnO-NPs (30 nm) close to 100 ppm (63.59 and 99.076 ppm) are the best to enhance tomato seeds germination since they promote metabolic activity to induce cell elongation, no phytotoxicity was observed. Itrouthwar et al [34] also evaluated ZnO-NPs (37 nm) in maize; they found that the concentration of 100 ppm exhibited the highest seed germination rate and seedling growth parameters as compared with zinc acetate (ionic control) and water (normal control).…”
Section: Discussionmentioning
confidence: 97%
“…6d). The maximum Zn 2+ uptake was determined at the 2000 mg/L as 20.32 mg/g dw (p < 0.05), while the control plants had 13.26 mg Zn 2+ /g dw. In other words, plants did not uptake the Zn 2+ in the environment when T-ZnO-NPs suspension were present at concentrations as high as 5000 mg/L (13.72 mg Zn/g DW) in the environment.…”
Section: Pot Experimentsmentioning
confidence: 91%
“…Recent studies show that the use of ZnONPs obtained via green synthesis at concentrations of 10-100 mg L −1 improved seed germination, the size of roots, shoots, and leaves, the number of roots, and the total fresh biomass in various plants: Triticum aestivum [24], Phaseolus vulgaris, Vigna angularis [25], and Hordeum vulgare [26]. In addition, ZnONPs obtained via green synthesis do not generate toxicity in concentrations of up to 100 mg L −1 in tomato seeds [27]. Sharma et al established that the concentration of ZnONPs at 20 mg L −1 improved the germination rate, the vigor of the seedlings, the production of reactive oxygen species (ROS), and the metabolic process of starch [28].…”
Section: Introductionmentioning
confidence: 92%